ERYTHEMA NODOSUM: A CUTANEOUS SIGN OF TUBERCULOSIS - Aisha Sajid; Muhammad Asim Ikram (Journal of University Medical & Dental College)
ABSTRACT Tuberculosis is a very common disease in developing countries often presenting in an atypical manner. High level of suspicion is required to diagnose it, thereby preventing its morbidity and mortality. We present two cases of young children presenting with erythema nodosum as a hypersensitivity reaction to tuberculoprotein without any evidence of active tuberculosis in the body.